Soustvarjanje podpore in pomoči učencem z učnimi težavami v izvirnem delovnem projektu pomoči - Mešl, Nina (Socialno delo, 2011)
Many research findings, dealing with the connection of school success and the success in somebody's further life, emphasize the importance of positive experiences in coping with challenges in school environment. As a respectful and responsible pupil's ally, the teacher certainly play the main role in co-creating new knowledge and in empowering the child as well. The interim analysis of the project "Professional foundations for further development and implementation of the concept 'learning difficulties in primary school'" shows that teachers see co-creation in a work relationship with children, having learning difficulties, as a good concept - not only on the conceptual level, but also on the level of its use at school.All the participants in this unique work project of help, where help and support are co-created, stress the progress in collaboration, show that steps towards solutions are easily agreed upon and that the child's voice is heard. The main concern about the (un)usefulness of the concept refers to the systematic obstacles connected with the time and organizational problems, which could impede the implementation of this model in the school system. On the other hand, teachers support the idea of including as many other pupils as possible to this unique project of help.
Keywords: učne težave; šolski uspeh; učenci; varovalni dejavniki; sodelovanje